2010
DOI: 10.1590/s0066-782x2010005000145
|View full text |Cite
|
Sign up to set email alerts
|

Há uma associação entre anti-inflamatórios não-esteroides e nefropatia induzida por contraste?

Abstract: Background: The association between the use of nonsteroidal anti-inflammatory drugs (NSAIDs) and acute or chronic renal failure is well documented, but evidence of such association between NSAIDs and Contrast-Induced Nephropathies (CIN) is not found in the indexed literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
3
2
1
Order By: Relevance
“…In the present study, we found that patients with NSAID use were significantly higher in the CIN group and multivariate regression analysis showed NSAID use as an independent predictor of CIN. In disagreement with our results, Diogo et al, stated that there is no association between NSAID use and CIN development [ 22 ]. Other independent predictors of CIN in multivariate regression analysis in our study were age > 60 years.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we found that patients with NSAID use were significantly higher in the CIN group and multivariate regression analysis showed NSAID use as an independent predictor of CIN. In disagreement with our results, Diogo et al, stated that there is no association between NSAID use and CIN development [ 22 ]. Other independent predictors of CIN in multivariate regression analysis in our study were age > 60 years.…”
Section: Discussioncontrasting
confidence: 99%
“…There is little good quality data about the relationship between these drugs and PC-AKI [ 27 ]. A retrospective cohort study showed that concurrent use of four or more nephrotoxic agents was significantly predictive for PC-AKI in patients given IV CM [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Da Silva et al46 evaluated the effects of nandrolone decanoate on the electrocardiographic profile, glycogen content and total-protein profile of skeletal and cardiac muscles, as well as the plasma albumin concentrations in rats, concluding that major cardiac changes are triggered at an early stage, which indicates a hierarchy in the sequence of changes that compromise the homeostasis of the body. Diogo et al47 evaluated the possible association between NSAIDs and Contrast-Induced Nephropathies and conclude that there was no association. Fagundes and Castro48 endeavored to determine the predictive value of resting heart rate before exercise stress testing for cardiovascular and all-cause mortality, concluding that it is an independent predictor of cardiovascular and all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%